Desenvolvimento do setor financeiro e crescimento econ??mico - Campos, Marcelo Ladvocat Rocha (2014)
This paper analyses the relationship between financial development and economic growth in a panel of 52 emergent countries from the year 2000 to 2012. We also verify the non-linearity hypothesis and the impacts of the 2008 financial cri-ses as a factor of disruption of this relationship. Additionally we verify an eventually divergent behavior between the two groups of countries. Although the hypothesis of positive impact was confirmed, we do not find any significant signal of non-linearity.